Bi Odegradability of Polyvinyl Alcohol in Sand for Resin Bonded Sand Casting Process - Hussein, N.I.S.; Ayof, M.N.; Yaakob, M.Y.; Salimon, S.H. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Resin bonded sand casting is widely used for manufacturing automotive parts, especially those made of aluminium alloys. In general, resin bonded sand casting use alkaline resin as binding agent. Typically, they are from non-biodegradable materials that have issues on reclamation and disposal of the sand as well as cause hazard to the environment. Therefore, a biodegradable resin consisting of Polyvinyl Alcohol (PVA) as one of the solution contents was developed to substitute the non-environmental friendly resin. The purpose of this investigation is to attest that PVA is a biodegradable material under natural environment. Weight loss quantification was used as a method to study the biodegradability of PVA and Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy were used to examine the molecular bonding as well as the morphological structure of the resin after biodegradation. The degradation process was evaluated by the weight loss and molecular structure of the PVA. At the end of this study, the weight loss of PVA is insignificant to show the biodegradation process. However, further investigation using FTIR and Raman spectroscopy methods; it is observed that there is a significant change in molecular and morphological structure of PVA.